A stochastic epidemic model of COVID-19 disease - Bardina, Xavier; Ferrante, Marco; Rovira, Carles (AIMS mathematics, 2020)
To model the evolution of diseases with extended latency periods and the presence of asymptomatic patients like COVID-19, we define a simple discrete time stochastic SIR-type epidemic model. We include both latent periods as well as the presence of quarantine areas, to capture the evolutionary dynamics of such diseases.